DETERMINATION OF THE COST COMPONENT IN THE SOCIAL COST-BENEFIT ANALYSIS OF ROAD PROJECTS IN SOUTH AFRICA - Pienaar, Wessel (The South African Journal of Industrial Engineering, 2021)
The article deals with the preferred approach to determine the cost component in the social cost-benefit analysis (SCBA) of road projects in South Africa. The article is in four parts. The first part, the introduction, provides the reasons why investment cost should be identified as a single cost entity in the SCBA of a road project, regardless of the criteria according to which a project is adjudicated. The second part discusses the principles that guide the determination of the social opportunity costs (SOC) of road projects. The third part identifies the two items that form the cost component of the SCBA of road projects; the SOC of (i) the land required to accommodate the road reserve, and (ii) the construction of the road. The cost component of the latter is sub-divided into labour, plant, equipment, fuel, materials, and normal profit. The section also details a recommended procedure to convert the financial budget of a road construction project to an estimate of its SOC. The fourth section draws some conclusions from the study.